Evaluasi Pola dan Rasionalitas Penggunaan Antibiotik pada Pasien Neonatus di Ruang NICU dan Perinatal RSUD Banjarnegara - Nastiti, Nindita Sari; Puspitasari, Ika; Nurulita, Nunuk Aries (Jurnal Kefarmasian Indonesia, 2023)
Neonates are particularly susceptible to infections caused by exposure to microorganisms during labor or shortly after birth. Some neonates require treatment in the NICU and perinatal rooms because of cases of infection that require antibiotics as therapy. This study aimed to determine the pattern of antimicrobial administration, antimicrobial rationality, and its relationship to clinical outcomes. This study used a cross-sectional design with prospective data collection using the medical record of neonates in the NICU and Perinatal rooms at RSUD Banjarnegara during November 2020-January 2021. The samples in this study were all neonatal patients who received antibiotics. Evaluation of antibiotics use was carried out using the Gyssens method. Descriptive analysis was conducted to determine the description of the research sample and the antibiotics used. A total of 131 samples had normal birth weight characteristics of 71%. The single antibiotic most frequently used as amoxicillin (21 patients), and the combination antibiotic was ampicillin+gentamicin (106 patients). The results of the evaluation using the Gyssens method showed that patients received 265 antibiotics, 85.55% were in category 0, 8.75% in category IIa, 3.8% in category IIIb, and 1.9% in category IIb. Of the 131 neonates treated, 124 patients were declared improved and 7 others died. The correlation between antibiotic rationality and clinical outcomes was analyzed by Chi-square, the result of the Asymp value. Sig (2-sided) 0.138 which means there is no relationship between the two. The rationality and effectiveness of clinical outcomes of antibiotics used during the study were considered good because the number of patients who were discharged with improved conditions was much greater than those who died.